Quality Work of Life, Organizationa Commitment and Organizational Citizenship Behavior as Determinants of Improving Higher Education Services in West Java - Muhammad Rizky Paramarta; Ilma Mufidah; Vip Paramarta; Rulia Rulia (Green Publisher Indonesia, 2025)
The success of an organization or company is heavily reliant on the behaviors exhibited by its employees, specifically those who are capable of fulfilling their responsibilities effectively, often exceeding the expectations set by their formal roles. Such behaviors do not occur spontaneously; rather, they are stimulated by work attitudes, including job satisfaction and organizational commitment. Additionally, these occupational attitudes, whether positive or negative, are influenced by the quality of work life (QWL) that employees experience, perceive, and derive from their workplace environment. The objective of this research was to assess the impact of QWL on both organizational commitment and organizational citizenship behavior (OCB), as well as its effect on the quality of services provided by permanent foundation lecturers in the management study programs of private universities in West Java. The research employed survey methods, specifically explanatory and descriptive approaches. The study was conducted within the management study programs of private universities in West Java, focusing on permanent foundation lecturers as the unit of analysis. The findings revealed a positive and significant relationship between QWL and organizational commitment, indicating that enhancing the quality of work life factors can lead to increased organizational commitment among permanent foundation lecturers towards their institutions. However, QWL did not demonstrate a significant direct effect on OCB. Both organizational commitment and OCB significantly affect service quality. Furthermore, improving the quality of lectures in teaching and learning activities for students can be achieved by fostering QWL, organizational commitment, and OCB.